Employing Artificial Intelligence in Developing Professional Development Programs for Teachers in the Sultanate of Oman in Accordance with Transformational Leadership Standards - Al-Buraiki, Ali Hamad; Belaid, Youssef Nait (Journal of Educational and Psychological Sciences, 2025)
Abstract: The study aimed to identify the role of transformational leadership dimensions (idealized influence, inspirational motivation, intellectual stimulation) and the level of employment of artificial intelligence tools (robots, cloud computing, augmented reality) to develop professional development programs for teachers in the Sultanate of Oman. The study adopted a descriptive survey methodology. The study population consisted of all public-school teachers in North Batinah and South Batinah governorates in the Sultanate of Oman. The researcher used a questionnaire as a research tool. The study sample included 373 male and female teachers in North and South Batinah governorates in the Sultanate of Oman. The study reached several results, the most important of which is that transformational leadership obtained an overall mean of 3.13, with a (moderate) response degree." As for the dimensions, the inspirational motivation dimension obtained the highest mean (3.36), followed by the idealized influence dimension (3.07), and thirdly, the intellectual stimulation dimension (2.98), all with a "moderate” response degree. The employment of artificial intelligence tools obtained an overall mean of 2.93 out of 5, with a "moderate" response degree. As for the dimensions, cloud computing came first with a mean of 3.26, followed by robotics (2.83), and thirdly, augmented reality (2.72), all with a "moderate” response degree. Based on the results, the study recommended organizing workshops and training programs for administrators on artificial intelligence tools and how to use them to develop professional development programs for teachers and providing the necessary resources and support for administrators to integrate artificial intelligence tools into teachers' professional development programs, in addition to suggestions for future studies on the topic.
Keywords: professional development programs; Sultanate of Oman; artificial intelligence; transformational leadership